(untitled) (Global Journal of Science Frontier Research, 2015)
Spate irrigation is a resource system, whereby flood water is emitted through normally dry wadi and conveyed to irrigable fields. Modernization of spate structures has been taking place in Raya valley since 1998 even though the efficiencies are not as intended. Initially the design standard was directly adopted from the conventional irrigation systems. Farmers were complaining that the implemented design standard was not appropriate with regards to their experiences. According to the professional’s perception, the reason for schemes failure could be poor management and lack of maintenance. Spate irrigation design development in Raya valley shows significant changes through time; like widening of intake, increasing of deflection angle, excluding of rain fall during design and reduction of irrigation time. The spate schemes with relatively best performance still have problems like; sedimentation around intakes, less spate flow and low performances. Therefore, understanding of the experience, wisdom and tradition of farmers is necessary during design and construction of spate irrigation.